Aceh Besar لترقية قدرة الطلاب على فهم المقروء بمعهد دار الإحسان PQ4R وطريقة Small Group Discussion مقارنة بين استخدام طريقة - Mardhatillah, Liza Safira; Hasyim, Syarifuddin; Ridha, Muhammad (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
The title of this research is "Comparison between the use of the Small Group Discussion Method and the PQ4R Method to Improve Students' Ability to Understand Reading at Dayah Darul Ihsan Aceh Besar". The researcher choose this title because most of students face difficulties in understanding what is read when reading the text, and they talk to each other and do not pay attention to the teacher when teaching reading. The cause of this problem is that the teacher does not use the right method in teaching reading skills. The purpose of this study was to determine the effectiveness of the use of the Small Group Discussion Method and the PQ4R Method, and to determine the results of the use of the Small Group Discussion Method and the PQ4R Method in improving students' reading comprehension skills. The population in this study were students of Ma'had Darul Ihsan grade 2 MTsS totaling 256 students. And the samples used were class VIII B (experimental class) which amounted to 33 students, and class VIII C (control class) which amounted to 33 students. The tools used by researchers to collect data are test instruments, namely pre-test and post-test questions, with descriptive statistical data analysis techniques, paired sample T-test, and independent sample T-test, using the SPSS 20 program. And the results This research is the use of the Small Group Discussion method and the PQ4R method effectively to improve students' ability to understand reading. And there is a comparison between the use of the Small Group Discussion method and the PQ4R method to improve students' reading comprehension skills.